2003
DOI: 10.1002/art.11025
|View full text |Cite
|
Sign up to set email alerts
|

C‐reactive protein as a regulator of autoimmunity and inflammation

Abstract: Metal acetylacetonates are effective latent catalysts for epoxy/anhydride systems. A screen test on the catalytic behavior of metal acetylacetonate shows that this system offers a wide range of curing latency and material properties. It can be inferred that the curing behavior is closely related to the bonding strength of the metal ion to the ligand. Isothermal kinetic study on the catalytic behavior of metal chelates with first‐row transition metal ions is conducted and analyzed by using an autocatalytic mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 71 publications
3
36
0
4
Order By: Relevance
“…High levels of serum CRP have been correlated to cardiovascular risks and other inflammatory or immune diseases (Tracy et al 1997;Du Clos 2003). Recently, elevated levels of CRP and hsp70 have been detected in frequent users of mobile phones (Balakrishnan et al 2014).…”
Section: J U S T a C C E P T E Dmentioning
confidence: 99%
“…High levels of serum CRP have been correlated to cardiovascular risks and other inflammatory or immune diseases (Tracy et al 1997;Du Clos 2003). Recently, elevated levels of CRP and hsp70 have been detected in frequent users of mobile phones (Balakrishnan et al 2014).…”
Section: J U S T a C C E P T E Dmentioning
confidence: 99%
“…Once the stimulus is no longer present, the CRP value starts falling with a half-life of 19 hours [3]. For many years, the value of CRP in healthy individuals has been considered to be less than 0.5 μ g/mL [4]. However, in a large study carried out in two different countries (comprising of 2291 males and 2203 females), Hutchinson et al found that CRP increases as the age of individuals increases [5].…”
Section: C-reactive Protein (Crp)mentioning
confidence: 99%
“…Currently, CRP and SAP are extensively used as biomarkers of various diseases and are targeted in cardiovascular disease treatment (Pepys et al, 2006). These proteins also have potentially broader applications in important diseases, including inflammation, infection and tissue damage (Du Clos, 2003;Ng et al, 2007;Xia and Samols, 1997).…”
Section: Introductionmentioning
confidence: 99%